Association of surface contamination by antineoplastic drugs with different working conditions in hospital pharmacies - Odraska, Pavel; Dolezalova, Lenka; Kuta, Jan; Oravec, Michal; Piler, Pavel; Synek, Stanislav; Blaha, Ludek (Archives of environmental & occupational health, 2014)
This study investigates the surface contamination levels of cyclophosphamide and platinum (a marker of platinum-containing drugs) in storage and preparation areas of hospital pharmacies and their relationship to working conditions surveyed by questionnaire. In total, 259 wipe samples were collected in 13 hospital pharmacies over 4 sampling campaigns. After sample extraction with acetate buffer, cyclophosphamide and platinum were determined using high-performance liquid chromatography-tandem mass spectroscopy (HPLC-MS/MS) and inductively coupled plasma mass spectrometry (ICP-MS). Depending on the sampling spot and campaign, median concentrations ranged from <2 to 61 pg/cm(2) and from <0.2 to 6.9 pg/cm(2) for cyclophosphamide and platinum, respectively. Statistical evaluation of monitoring data revealed that the contamination level was significantly influenced by laboratory throughput (expressed as number of chemotherapies prepared per week), personnel expertise (ie, participation of pharmacists with academic education in drug admixture activities), and surface material.
Keywords: Workplace; protinádorové látky; Occupational Exposure; Cyclophosphamide; vysokoúčinná kapalinová chromatografie; Česká republika; tandemová hmotnostní spektrometrie; platina; pracovní expozice; Platinum; nemocniční lékárny; Chromatography, High Pressure Liquid; Czech Republic; lidé; Equipment Contamination; Humans; cyklofosfamid; Pharmacy Service, Hospital; Tandem Mass Spectrometry; kontaminace zdravotnického vybavení; pracoviště; Antineoplastic Agents